(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The dynamics of changes in absolute parameters of linear parameters of the muscular stomach in the postnatal ontogenesis of domestic chickens has been studied. It was found that the absolute index of linear parameters increases more intensively from the first 3 days to the 16-day age of postnatal ontogenesis and up to 280 days, this process continues in stages, and does not change significantly at 420 and 570 days. It was revealed that the absolute index of the muscular stomach increases intensively from 3 days to 85 days and reaches the highest index in 280 days of postnatal ontogenesis. It was determined that the growth coefficient of morphometric parameters of the muscular stomachs of chickens in the period from 3 days to 570 days of age is significantly higher in their mass than linear parameters.